Education in world history - Johnson, Mark S., 1960- author.
1 online resource (vi, 252 pages).
Keywords: "Education in World History shows how broad currents in transnational history have interacted with trends in educational organization and teaching practices over time. From antiquity and early Classical societies to present day, this book highlights the ways in which changes in religious and intellectual life and economic patterns in key world regions have generated developments in education. Since the postclassical period, cross-cultural connections have also influenced educational change. In more recent times, transnational dialogues and mobility have played a vital role in shaping educational patterns. Ranging through South and East Asia, Africa, Europe, and the Americas, the book also considers how the impact of modern forces, such as industrialization and nationalism, have transformed education in fundamental ways. Throughout the volume, Mark S. Johnson and Peter N. Stearns emphasize the tensions between elite and state educational interests and more diverse popular demands for access and, often, for more innovative pedagogy. Suitable for introductory world history and history of education courses, this lively overview reconsiders the history of education from the perspective of world and comparative history"--